Socially connected while apart: the use of technology to increase social connection between nursing home residents and their relatives - Akhtar, Sehrish Andleeb (Frontiers in Public Health, 2024)
This study examines whether the use of a communication technology can enhance social connectedness among nursing home residents in Norway. The concept of social connectedness suggest that positive and significant interpersonal relationships can help reduce the risk of loneliness and social isolation among older adults and can be beneficial for both their health and overall wellbeing. In recent years, technology has been increasingly utilized as a method to overcome physical distances and to keep families connected. Although the use of digital solutions among older people has increased in recent years, few studies have addressed the use and impact of such technologies within a nursing home context. This study examines whether Kompa communication technology designed specifically for older people with little to no digital experiencecan enhance social connectedness among older nursing homes residents. A total of 225 residents participated in the study, making it one of the few quantitative studies that examine the use of communication technologies in nursing homes at such a large scale. The study combines two sources of data. First, survey data were collected over a 14-month period, in three different waves, at all public nursing homes in Oslo municipality. The survey data was collected prior to implementing Komp, with a twoand six-months follow-up after the implementation. The second source of data used in the study is a highly detailed weekly datastream from each Komp-device, which provides an objective measure of the frequency of contact between the residents and their families. The two sources of data are combined and analyzed using multiple regression analysis. The findings from the regression analysis shows a positive and significant relationship between use of Komp and increased social satisfaction among nursing home residents. The results indicate that Komp is a feasible communication tool to help nursing home residents maintain relations with their families, implying that the intervention has the potential to enhance social connectedness and can be a feasible strategy to be connected to the world outside the care homes.